Effects of Green Tea on Cognitive Function and Mental Status: Emerging Evidence - Liang, Wenbin; Lee, Andy (Nova Science, 2013)
Green tea is usually prepared by adding boiling water to dried tea leaves, which are made from the plant Camellia Sinensis. Worldwide, tea is the second most popular beverage after water. Similar to alcohol and coffee, drinking of green tea can produce pleasant feelings. In other words, consumption of green tea is partly due to its biological effects on cognitive function and emotions. To date, extensive epidemiological, clinical and experimental studies have shown that green tea drinking is beneficial to many aspects of physical health. There is also emerging evidence suggesting that key compounds of green tea may promote mental status and health of the central nervous system. The most promising candidates are L-theanine and green tea catechins. This commentary reviews recent findings from experimental and epidemiological studies on the neurological effects of green tea, and discusses possible mechanisms of action.